Comparative effects of Moringa oleifera and ascorbic acid on biochemical changes induced by subchronic lead toxicity in male Wistar rats - A. Usman; M.U. Kawu; M. Shittu; A. Saleh; G. Bilbonga (Elsevier, 2022)
This experiment was aimed at comparing the effects of Moringa oleifera (MO) and ascorbic acid (AA) on biochemical changes induced by subchronic lead (Pb) toxicity in male Wistar rats. A total of 36 adult male Wistar rats were used for the work with grouping and dosing as follows; Group I was given distilled water (2 mL) only, Group II rats were administered Pb (190 mg/kg), Group III received Pb (190 mg/kg) + MO (500 mg/kg). While rats in groups IV, V, and VI were administered Pb (190 mg/kg) + AA (100 mg/kg), Pb (190 mg/kg) + MO (500 mg/kg) + AA (100 mg/kg) and Pb (190 mg/kg) + MO (250 mg/kg) + AA (50 mg/kg) respectively. Administration of all agents was done daily by oral gavage for a period of 6 weeks. Result showed decreased alanine amino transferase (ALT), aspartate amino transferase (AST) and alkaline phosphatase (ALP) levels in group II compared to other groups. Creatine kinase (CK) activity was significantly (P ≤ 0.05) higher in group II compared to other groups while lactate dehydrogenase (LDH) activity was significantly decreased in group II compared to other groups. Total protein, albumin and globulin concentrations were not significantly (P ≥ 0.05) different across all groups. The malondialdehyde concentration in group 2 was higher (P < 0.001) compared to other groups. A decrease (P < 0.01) was observed in superoxide dismutase activity in group 2 compared with groups 3 and 6. There was no significant difference (P > 0.05) in catalase and glutathione peroxidase activities among groups. This study depicts the detrimental effects of Pb on biochemical parameters in the rats. Treatment with AA (50 mg/kg) and MO (250 mg/kg) gave better amelioration of the toxic effects of Pb.